Local Community Awareness in Inclusive Tourism Development in Tegaren Village, Trenggalek - Herlina Suksmawati; Praja Firdaus Nuryananda; Leily Suci Rahmatin (Nusantara Science and Technology Proceedings, 2023)
Currently, it is very important to build the tourism sector based on an awareness of inclusivity. This article is a summary of the community service activities that have been carried out in the Tegaren Tourism Village, Trenggalek Regency, East Java. The program implementation team has tried to take the essence of the various community service activities that have been carried out. The core results of these activities can be divided into two parts, namely 1) awareness of inclusivity in Tegaren has existed for a long time, along with the development of this tourist village and 2) awareness of this inclusivity has facilitated collaboration with stakeholders, which in turn helps Tegaren plans concrete steps to develop tourism in the village, including through virtual tours. The program implementation team uses a variety of participatory approaches in planning, implementing, and evaluating community service programs in Tegaren. This approach includes participatory rural appraisal (PRA), asset-based community development (ABCD), collaborative partnerships, and community-based tourism (CBT). By implementing these participatory approaches, the implementation team also gives a significant role to the community or local people in Tegaren. This role further strengthens collective awareness, including awareness of inclusivity.